Strategies To Increase The Competitiveness Of Private Madrasah Aliyah MA YPPA Cipulus Purwakarta And MA Al-Muthohhar Purwakarta - Sulaiman, Akhmad; Wasliman, IIm; Sudrajat, Adjat; Mulyanto, Agus (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Education has an important role in human life. In its management, formal education in Indonesia at the elementary and secondary levels is carried out in educational units called schools or madrasas. Today's education units face challenges, both from similar competitors and the demands and expectations of society. For this reason, educational units need to be competitive. Even so, Madrasah Aliyah must also have competitiveness. From this background, the researchers set out to study by presenting a study entitled Strategies for Increasing the Competitiveness of Private Madrasah Aliyah at MA YPPA Cipulus Wanayasa and MA Al-Mutohhar Plered Purwakarta. The purpose of this study is a qualitative approach with a descriptive method that describes strategies for increasing competitiveness in the MA YPPA Cipulus Wanayasa Purwakarta and MA Al-Muthohhar Plered Purwakarta. Data collection was carried out by interview, observation and literature study, using qualitative analysis. Based on the research results, madrasas scan the internal and external environment, have a number of advantages and also weaknesses, Madrasas formulate strategies to increase competitiveness in the form of missions, goals, strategies and policies, implement strategies to increase competitiveness in madrasas, Madrasas evaluate and control strategies for increasing competitiveness competitiveness and madrasas that are competitive are relatively in demand by the community. observation and literature study, using qualitative analysis. Based on the research results, madrasas scan the internal and external environment, have a number of advantages and also weaknesses, Madrasas formulate strategies to increase competitiveness in the form of missions, goals, strategies and policies, implement strategies to increase competitiveness in madrasas, Madrasas evaluate and control strategies for increasing competitiveness competitiveness and madrasas that are competitive are relatively in demand by the community. observation and literature study, using qualitative analysis. Based on the research results, madrasas scan the internal and external environment, have a number of advantages and also weaknesses, Madrasas formulate strategies to increase competitiveness in the form of missions, goals, strategies and policies, implement strategies to increase competitiveness in madrasas, Madrasas evaluate and control strategies for increasing competitiveness competitiveness and madrasas that are competitive are relatively in demand by the community